2015
DOI: 10.1177/0143831x15581424
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health and safety of temporary and agency workers

Abstract: Previous quantitative studies have established a link between precarious work and occupational health and safety (OHS). Using an ethnographically informed qualitative approach, this article investigates the workplace experiences of different types of precarious workers, in particular those who are directly-employed temporary workers and those who are engaged through an agency. Drawing on the work of Andrew Hopkins, the article finds cultural practices that lead to worsened OHS experiences for those who are eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…This study reports an increased risk of reversible airway obstruction in casual workers. This finding is consistent with previous studies which demonstrated casual workers to have an increased likelihood of exposure to occupational hazards and poorer occupational health and safety outcomes compared to permanent workers . This is due to a number of factors including casual workers using poor quality personal protective equipment; subjected to constant changes in their tasks; pressurized to take on manual and more hazardous work with limited supervision or training; and are usually not confident to raise safety issues for fear of having their jobs terminated …”
Section: Discussionsupporting
confidence: 90%
“…This study reports an increased risk of reversible airway obstruction in casual workers. This finding is consistent with previous studies which demonstrated casual workers to have an increased likelihood of exposure to occupational hazards and poorer occupational health and safety outcomes compared to permanent workers . This is due to a number of factors including casual workers using poor quality personal protective equipment; subjected to constant changes in their tasks; pressurized to take on manual and more hazardous work with limited supervision or training; and are usually not confident to raise safety issues for fear of having their jobs terminated …”
Section: Discussionsupporting
confidence: 90%
“…Although in Western Europe the general rate of occupational accidents has decreased during the last 30 years, there seems nevertheless to have been a noteworthy recent increase among atypical workers and foreign workers (Hopkins, 2015;Howes, 2011). This trend of greater risks for non-nationals is also borne out in other European locations.…”
Section: Safety Risk Well-being and Organisationsmentioning
confidence: 99%
“…Of these, 16 reported contracting relationships principally between firms and individuals, although some (e.g. Hopkins, 2017;Hakansson and Isidorsson, 2016;Stauss-Raats, 2019;Underhill and Quinlan, 2011) reported the recruitment of individuals through an employment agency. A further 33 reported outsourcing principally between firms.…”
Section: Descriptive Summarymentioning
confidence: 99%